Medical errors in primary care clinics - a cross sectional study - Khoo, Ee Ming; Lee, W.K.; Sararaks, S.; Samad, A.A.; Liew, S.M.; Cheong, A.T.; Ibrahim, M.Y.; Su, S.H.C.; Hanafiah, A.N.M.; Maskon, K.; Ismail, R.; Hamid, M.A. (BMC, 2012)
Background: Patient safety is vital in patient care. There is a lack of studies on medical errors in primary care settings. The aim of the study is to determine the extent of diagnostic inaccuracies and management errors in public funded primary care clinics. Methods: This was a cross-sectional study conducted in twelve public funded primary care clinics in Malaysia. A total of 1753 medical records were randomly selected in 12 primary care clinics in 2007 and were reviewed by trained family physicians for diagnostic, management and documentation errors, potential errors causing serious harm and likelihood of preventability of such errors. Results: The majority of patient encounters (81) were with medical assistants. Diagnostic errors were present in 3.6 (95 CI: 2.2, 5.0) of medical records and management errors in 53.2 (95 CI: 46.3, 60.2). For management errors, medication errors were present in 41.1 (95 CI: 35.8, 46.4) of records, investigation errors in 21.7 (95 CI: 16.5, 26.8) and decision making errors in 14.5 (95 CI: 10.8, 18.2). A total of 39.9 (95 CI: 33.1, 46.7) of these errors had the potential to cause serious harm. Problems of documentation including illegible handwriting were found in 98.0 (95 CI: 97.0, 99.1) of records. Nearly all errors (93.5) detected were considered preventable. Conclusions: The occurrence of medical errors was high in primary care clinics particularly with documentation and medication errors. Nearly all were preventable. Remedial intervention addressing completeness of documentation and prescriptions are likely to yield reduction of errors.